Home-based exercise in patients on maintenance dialysis: a systematic review and meta-analysis of randomized clinical trials - Battaglia, Yuri; Amicone, Maria; Mantovani, Alessandro; Combe, Christian; Mitra, Sandip; Basile, Carlo (Nephrology, dialysis, transplantation, 2023)
The impact of home-based exercise on physical performance and quality of life (QoL) in patients on maintenance dialysis has not yet been fully established. We searched four large electronic databases to identify randomized controlled trials (RCTs) reporting the impact of home-based exercise interventions vs. usual care or intradialytic exercise interventions, on physical performance and QoL in patients on dialysis. The meta-analysis was performed using fixed effects modeling. We included 12 unique RCTs involving 791 patients of various ages on maintenance dialysis. Home-based exercise interventions were associated with an improvement of walking speed at the 6 Minutes Walking Test (6MWT; 9 RCTs; pooled weighted mean differences [WMD]: 33.7 meters, 95% confidence interval [CI] 22.8 - 44.5; p<0.001; I2 = 0%) and in aerobic capacity as assessed by the peak oxygen consumption (VO2 peak; 3 RCTs; pooled WMD: 2.04 ml/kg/min, 95% CI 0.25 - 3.83; p = 0.03; I2 = 0%). They were also associated with improved QoL, as assessed by the Short Form (36) Health (SF-36) score. Stratifying the RCTs by control groups, no significant difference was found between home-based exercise and intradialytic exercise interventions. Funnel plots did not reveal any significant publication bias. Our systematic review and meta-analysis showed that home-based exercise interventions for three to six months were associated with significant improvements in physical performance in patients on maintenance dialysis. However, further RCTs wih a longer follow-up should be conducted to assess the safety, adherence, feasibility, and effects on QoL of home-based exercise programs in dialysis patients.